The nexus between management control systems, firm performance, green innovation and social media networking in Indonesian real estate companies - Ida Farida; Doddy Setiawan (Innovation & Management Review, 2025)
Purpose - This study aims to explore the correlation between Management Control Systems, Green Innovation, Social Media Networks, and Company Performance in medium-sized construction and real estate firm in Indonesia. Design/methodology/approach - This research method uses quantitative approach. The sample selection technique uses simple random sampling. The analytical method in this study uses structural equation models based on variance. Statistical test tool used, is Smart PLS 3.0. Findings - The management control systems have a significant and positive impact on social media networks, green innovation, and company performance in the upper-middle-class construction and real estate businesses in Java. Furthermore, social media networks and green innovation were found to mediate the strong relationship between management control systems and firm performance in medium-sized construction and real estate businesses in Java. Research limitations/implications - This research should provide a detailed, technical, and structured explanation of how companies assess suitability standards for implementing green innovation in Indonesia's construction and real estate sectors. Social implications The finding emphasize the importance of the management control system in enhancing firm performance. If, the elements of the management control system are met or adequate, it can improve the performance of those in charge, leading to satisfactory performance. Originality/value - This finding is the first of its kind in Indonesia. It will contribute to shaping future development policies for government and private projects, ensuring they are more advance and environmentally conscious.
Keywords: Q01; F63; G32; O36; 650; Management control system; Green innovation; Economic development